Turn-Taking Strategy on Donald Trump and Joe Biden 2020 Presidential Debate - Muhammad Farhan Aslam; Ambalegin Ambalegin (Hasanuddin University, 2025)
This qualitative research study examines the turn-taking methods utilized during the presidential debate between Joe Biden and Donald Trump, with a focus on utterances and written words. Employing an observational approach (Sudaryanto, 2015), data were collected by closely observing the debate and recording pertinent remarks through note-taking. Several steps were followed in data collection, including initial observation of the debate, transcription of the debate script, and highlighting remarks indicative of turn-taking strategies as proposed by Stenström (1984). Data analysis followed the identification method outlined by Creswell and Poth (2014), involving multiple viewings of the debate video to comprehend the turn-taking methods and categorize the transcriptions to denote their application. The study identified 29 turn-taking strategies based on Stenström's (1984) theory, categorized into three groups: initiating the turn (starting up, taking over, and interrupting), maintaining the turn (utilizing filled pauses, lexical repetition, and introducing new topics), and relinquishing the turn (prompting, appealing, and conceding). These findings offer valuable insights into communication strategies within high-stakes political debates and contribute to a deeper understanding of the interplay between theory and qualitative research.